2019
DOI: 10.4025/actascitechnol.v41i2.36709
|View full text |Cite
|
Sign up to set email alerts
|

Influence factors in the adjustment of parameters of the modified first-order kinetics equation used to model constructed wetland systems

Abstract: The aim of the present work was to evaluate the relationship between the hydraulic retention time power parameter (n) of the modified first-order kinetic mathematical model (MFOKM) with the hydraulic dispersion number (d) and the organic matter degradability, obtained from the ratio of chemical and biochemical oxygen demands (COD/BOD) along the length of horizontal subsurface flow constructed wetlands (HSSF-CWs). For this purpose, unplanted HSSF-CWs prototypes of equal volumes and length/width ratios (L W-1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…MWW treatment plants are meticulously designed to cater to the level of purification required for the product. As de Matos et al [21] described, these treatments can span multiple stages, including preliminary, primary, secondary, and tertiary.…”
Section: Municipal Wastewater Treatment Plantsmentioning
confidence: 99%
“…MWW treatment plants are meticulously designed to cater to the level of purification required for the product. As de Matos et al [21] described, these treatments can span multiple stages, including preliminary, primary, secondary, and tertiary.…”
Section: Municipal Wastewater Treatment Plantsmentioning
confidence: 99%
“…Matos et al [28] observed graphically and using Pearson's coefficient (−0.985) that Likewise, for low initial concentrations, the degradability would be smaller and the organic material more recalcitrant. This would characterize the conditions of a pre-treated sewage (primary, secondary or tertiary effluent), in which there is remaining material that is more difficult to degrade, i.e., having a k value smaller and more uniform.…”
Section: Association Between N Coefficient and Inffluent Cod Concentr...mentioning
confidence: 99%
“…Matos et al [28] observed graphically and using Pearson's coefficient (−0.985) that the value of (n) is strongly associated with the deterioration grade of organic matter (OM). In summary, the greater the magnitude of variation in OM concentrations at the beginning of CWs, the lower the value of n.…”
Section: Association Between N Coefficient and Inffluent Cod Concentr...mentioning
confidence: 99%